Revival of the Russian chemical industry during the Soviet period (1917–1927). Part 4 - K. S. Guzev (Разработка и регистрация лекарственных средств, 2022)
The fourth chapter presents V. N. Ipatiev's memoirs about the preparation and celebration of the 200th anniversary of the Russian Academy of Sciences and the next Mendeleev Congress. About repeated foreign business trip with commercial and scientific purposes. During this trip, Ipatiev managed to visit a large number of familiar chemists, heads of chemical faculties of German, French, Belgian universities and laboratories of leading chemical departments. His scientific activity during the final period of his life in Russia, before emigrating to Germany, and later to the USA, is described.